Decoding of second order Reed-Muller codes with a large number of errors - Bassem Sakkour (Proceedings of the IEEE ITSOC Information Theory Workshop 2005 on Coding and Complexity (ITW 2005) Rotoruan New Zealand, August 29 - September 1, 2005, 2005)
Second order Reed-Muller codes are considered over a binary symmetric channel. We present a modified version of V.M Sidel'nikov and A.S. Pershakov algorithm, Problemy Peredachi Informatsii 1992, that has complexity of order n/sup 2/log(n). Experimental results show that the algorithm corrects most error patterns of weight up to n/2(1-e) given that e exceeds n-1/3. This outperforms other decoding algorithms known for RM codes. Decoding performance for known algorithms has been evaluated and the results correspond to asymptotic performance for these algorithms.